Investigating of Vocabulary Learning Strategies Used by Undergraduate Students - Selpi binti Suhaedi; Nanning (Institut Agama Islam Negeri Parepare, 2018)
The present study aimed to investigate Vocabulary Learning Strategies (VLSs) used by undergraduate students (S1) of 6th semester and how they learned or acquired VLSs. In addition, the study compares the use of VLSs between low and high achievers of undergraduate students that consisted of 30 students. An explanatory sequential mixed research method was implemented in this study. The corroboration was used employing a questionnaire adapted from Schmitt’s taxonomy (Classification of VLSs) as the instruments. As for the qualitative approach, the writer conducted interviews to explore how the students acquired VLSs. The research report showed that the mean score indicated the uses of Determination strategies are most frequently used by both of achiever. Likewise, the least frequently used vocabulary learning strategy was Social strategies (Consolidation). There were no great differences found in using vocabulary learning strategies between the low and high achievers and they learn the most frequently used strategy in several situations such as, course, organization, English club, media, and etcetera. Effective vocabulary learning and teaching strategies need to be incorporated into students’ vocabulary learning process.